Research on post-processing development technology for four-axis turn-milling compound machining with Siemens 840Dsl CNC system - Li, Guan-lin; Zhang, Qian; Yue, Hai-bao; Wang, Peng-wei; Ma, Jian-wei; Xie, Ying-hao; Ye, Tao (International journal of advanced manufacturing technology, 2025)
Large curved components such as wheel hubs, case covers, and blisks play a crucial role in high-end equipment manufacturing due to their specialized functions. As the demand for higher precision, greater efficiency, and increasingly intricate geometric shapes continues to rise, the need for advanced machining equipment with improved precision, structural complexity, functional integration, and machining stability becomes more urgent. Traditional machining methods, with their relatively simple structures and limited functionality, are progressively proving inadequate to meet these evolving requirements. In response, multi-axis turn-milling composite machining offers innovative solutions to these challenges. However, adapting this technology to handle multi-surface, multi-angle, and asymmetric features in complex geometries introduces significant difficulties, particularly in automatic programming and post-processing. This complexity underscores the need for research into adaptive process planning and programming techniques specific to multi-axis turn-milling composite machining, especially when considering the structural configurations and motion transmission characteristics of such systems. An important focus of this research is to develop a method for planning the motion trajectories of different feed axes, and to match these to generate precise machining G-codes with specific instruction sets. The goal is to ensure coordinated operation when multiple feed axes are engaged simultaneously. This study focuses on the Siemens 840Dsl Computer Numerical Control System and introduces a post-processing technology aimed at enhancing toolpath planning for four-axis turn-milling composite machining, striking a balance between trajectory accuracy and programming efficiency. Firstly, it is necessary to establish the topology and low-order body array list for the XYZC-type four-axis turn-milling composite machine tool, based on its specific structural configuration and motion transmission relationships. By employing homogeneous coordinate transformation, the kinematic equations are formulated and solved for both forward and inverse kinematics. Next, the process incorporates cutter location point denseness constrained by interpolation trajectory errors, as well as cutter location point sparsity adjustments based on the angles between adjacent points. These adjustments are designed to optimize toolpaths while maintaining the necessary balance between trajectory accuracy and programming efficiency. Finally, the post-processing program for the four-axis turn-milling composite machine tool is developed using the UG/Post Builder tool, implementing an integration algorithm. The resulting machining code is validated through CIMCO Edit software and then applied in practical machining experiments on the PIETRO CARNAGHI (AC36TMY3000 XYZC-type) four-axis turn-milling composite machine tool. This research provides a foundational framework for optimizing toolpaths and developing post-processing programs for four-axis turn-milling composite machining. It holds significant potential for improving the quality and efficiency of machining large and complex curved components, marking an important advancement in the field of high-precision equipment manufacturing.